In search of disambiguation: development of eye drop bottle sleeves to aid in identification and survey among possible users. A cross-sectional study - Costa, Ana Luiza Fontes de Azevedo; Martins, Thiago Gonçalves dos Santos; Santos, Vagner Rogério dos; Schor, Paulo (São Paulo Medical Journal, 2022)
BACKGROUND: Considerable numbers of individuals present low vision, blindness, illiteracy and other conditions that could possibly impair their identification of medications, such as eye drops. Through helping these individuals to identify their eye drops, they can achieve greater autonomy. Misidentification can be avoided through use of multisensory sleeves that can be adapted to most eye drop bottles. Correct use of eye drops is important for preventing progression of diseases like glaucoma that could potentially lead to blindness. OBJECTIVE: To develop bottle sleeves to aid in identification of eye drops and then interview a group of possible users to evaluate the acceptance of the solution. DESIGN AND SETTING: Cross-sectional survey performed at an ophthalmological clinic in São Paulo (SP), Brazil. METHODS: We describe the development of multisensory sleeves to assist in identification of eye drops. To assess the acceptance of this solution, we interviewed 18 patients who were currently using three or more types of eye drops. RESULTS: We developed four prototypes for eye drop bottle sleeves and conducted an acceptance test on them. Most of the patients who answered the survey about the sleeves were elderly. Most (95%) reported believing that the sleeves would help reduce the risk of mixing up eye drops with other medications that also dispense drops. They also believed that these would increase their autonomy in using eye drops. CONCLUSION: The solution presented was well accepted and may help increase safety in using eye drops through preventing misidentification.